Direct conversion of lignin to high-quality biofuels by carbon dioxide-assisted hydrolysis combined with transfer hydrogenolysis over supported ruthenium catalysts - Kim, Han Ung; Kim, Jong Wha; Tran, Ngoc Tuan; Limarta, Susan Olivia; Ha, Jeong-Myeong; Park, Young-Kwon; Jae, Jungho (Pergamon Press Ltd., 2022)
The central challenge in the biomass-to-fuel conversion process lies in the development of a catalytic strategy for the full utilization of each biomass component, to realize maximum carbon efficiency. In particular, the effective conversion of lignin into biomass is a major bottleneck because of its recalcitrant structure, necessitating the development of new catalytic reaction systems. Here, for the first time, a new hybrid reaction approach involving carbon dioxide-assisted hydrolysis and transfer hydrogenolysis using alcohols as hydrogen donors in a single reactor was investigated for the effective depolymerization of lignin. Specifically, the supercritical carbon dioxide-induced carbonic acid resulted in considerable acidity in the water/alcohol reaction media, enhancing the hydrolytic depolymerization of solid lignin to soluble oligomers. The addition of supported metal catalysts (e. g., Ru/C) further depolymerized the oligomers to monomeric phenols through hydrogenolysis using the hydrogen produced in situ from alcohol solvents. Systematic parameter studies on the carbon dioxide pressure, water/alcohol mixing ratio, type of alcohol, catalyst addition, and temperature were performed to elucidate the synergistic role of carbon dioxide catalysis and transfer hydrogenolysis in lignin depolymerization. Overall, for organosolv lignin, high biocrude oil and monomer yields of ~75 and ~21.4 wt%, respectively, were successfully obtained at 300 ? and 40 bar-carbon dioxide after 4 h using a water/ethanol cosolvent at a 25:75 ratio and Ru/C as a catalyst. The effectiveness of the combined carbon dioxide catalysis and transfer hydrogenolysis approach was further demonstrated in the direct depolymerization of lignin in raw biomass.